2011
DOI: 10.4209/aaqr.2011.05.0065
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of AERMOD and ADMS-Urban for Total Suspended Particulate Matter Concentrations in Megacity Delhi

Abstract: Regulatory models are useful tools for air quality management. However, application of models without proper evaluation may lead to erroneous conclusions and thus systematic model evaluation studies are essential prior to model application. Often, models are evaluated for a specific source and climatic condition and then find application to another source and climatic condition without this realization. In this context, two well known regulatory models namely; AERMOD (07026) and ADMS-Urban (2.2) are applied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…It may be because, resuspension of particulate matter might be more or some emission sources like fugitive were missed in emission inventory which was used to run this model. It is also well known that models are underestimating for PM in air quality modeling study (Mohan et al 2011;Rood 2014).…”
Section: Resultsmentioning
confidence: 98%
“…It may be because, resuspension of particulate matter might be more or some emission sources like fugitive were missed in emission inventory which was used to run this model. It is also well known that models are underestimating for PM in air quality modeling study (Mohan et al 2011;Rood 2014).…”
Section: Resultsmentioning
confidence: 98%
“…A number of published articles have shown that AERMOD is an accurate and reliable modeling system. Using empirical data in a variety of different scenarios, these studies showed that "estimated values agree with the observed concentrations within a factor of two" (Mohan et al, 2011). Moreover, AERMOD has consistently proven to be the most efficient of all the available air modeling systems, as well as produce the least amount of bias.…”
Section: Methodsmentioning
confidence: 93%
“…It is developed by the USEPA (Cimorelli et al, 2004). AERMOD has been used for environmental impact assessment in many countries (Seangkiatiyuth et al, 2011;CPCB, 2008;Kumar et al, 2015;Mohan et al, 2011)). In India, ISCST3 is regulatory model but results of AERMOD are accepted because it has been upgraded with many algorithms for getting more accurate results.…”
Section: Aermodmentioning
confidence: 99%